POPLITEAL VEIN ANEURYSMS - Sousa, Pedro Pinto (2018)
Popliteal vein aneurysm is a rare but potentially fatal entity due to possible thromboembolic complications. The purpose of this paper is to describe two institutional cases and to review the literature. In one case the diagnosis was made after the occurrence of symptomatic pulmonary embolism and in another, incidentally. In both cases the treatment was by conventional surgery without perioperative complications. From the literary review, a total of 43 popliteal vein aneurysms published between 206 and 2016 were analyzed.